Parts per Million Level, Green, and Magnetically-recoverable Triazole Ligand-stabilized Au and Pd Nanoparticle Catalysts - Su, Song; Yue, Guozong; Huang, Deshun; Yang, Guiying; Lai, Xinchun; Zhao, Pengxiang (RSC advances, 2015)
Triazole ligands with carboxylic acid at one termini and polyethylene oxide (PEO) at the other termini are synthesized via “click” chemistry and subsequently attached onto the Fe 3 O 4 surface by ligand-exchange reactions. Then the small-sized Au or Pd nanoparticles are encapsulated into this nanocomposite by their mild coordination with triazole, yielding efficient, green and magnetically-recoverable nano catalysts.